Analisis Tingkat Pendapatan UMKM Di Jalan Garu II A Medan - Muhammad Hadid Fahlifi; Dina Safira; Putri Ade Pratiwi; Sasya Triamanda Barimbing; Nirmawan (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
The main focus of this study is to identify the income levels of MSMEs that depend on the variables of capital, business location, working hours, and entrepreneur education. The sample for this study consists of 20 MSMEs located on Jalan Garu II-A, Medan. This research uses a quantitative method with data collected directly from primary sources. The data collection technique employed by the researcher is through questionnaires. For data analysis, multiple linear regression is used and processed using IBM SPSS version 26. Based on the research output, it was found that capital (X1), business location (X2), and entrepreneur education (X4) have a significant impact on business income (Y), with their effective contributions to business income being 20.2 for capital (X1), 26.9 for business location (X2), and 17.9 for entrepreneur education (X4). Meanwhile, Working Hours (X3) does not have a significant impact on business income (Y), with an effective contribution of 7.0.